Pengaruh Tingkat Pemahaman Akuntansi, Persepsi Karir, Dan Prestasi Akademik Terhadap Niat Untuk Mengambil Sertifikasi Profesi Chartered Accountant (CA) Motivasi Sebagai Variabel Moderasi (Studi Kasus Pada Mahasiswa S1 Akuntansi Di Universitas Muhammadiyah - Astuti, Agnes Mei; Zanaria, Yulita; Hendri, Nedi (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This type of quantitative research uses a comparative causal study, namely analysis, that is directed to investigate cause-and-effect relationships. Data was collected using a questionnaire method and processed using SPSS Statistics 25 with a sample of 55. This study aimed to determine the effect of the level of accounting understanding, career perception, and academic achievement on the intention to take Chartered Accountant (CA) professional certification motivation as a moderating variable. On accounting students at the University of Muhammadiyah Metro. The results showed that (1) the relationship between the level of accounting understanding and the intention to take chartered accountant (CA) professional certification did not have a significant effect (2) career perception significantly influenced the intention to take chartered accountant (CA) professional certification (3) achievement relationship. There is no significant effect on the academic intention to take chartered accountant (CA) professional certification (4) motivation can moderate the relationship between the level of accounting understanding and intention to take chartered accountant (CA) professional certification (5) motivation can moderate the relationship between career perception and intention to take chartered accountant (CA) professional certification (6) motivation can moderate the relationship between academic achievement and intention to take chartered accountant (CA) professional certification.